PSIKOEDUKASI TENTANG POLA ASUH EFEKTIF ANAK DI ERA DIGITAL - Andriani, Rezah (Khidmah, 2022)
Advances in technology and information today are almost unstoppable. All dimensions of human life have been entered and influenced by technology and information, including in the world of education. Advances in technology and information bring positive and constructive benefits or values. The development of technology and information today, especially the use of digital devices, has affected children's lives. Children need guidance and direction from parents to use digital media wisely, for that we need psychoeducation to parents about how effective parenting is for children in the digital era, as well as the role of parents in guiding children in the digital era and use management gadgets for kids. This activity was held on August 5, 2022 at PMB Herasdiana Palembang with 17 participants, namely parents who have children aged 4-6 years. The results of the evaluation of the pre-test assessment obtained an average score of 79.64 and an average post-test score of 82.88 so that there was an increase in the knowledge and understanding of parents about effective parenting for children in the Digital